2019
DOI: 10.1111/sifp.12102
|View full text |Cite
|
Sign up to set email alerts
|

Family Formation Goals Among Sexual and Gender Minority Individuals in Urban India

Abstract: Sexual and Gender Minority (SGM) individuals ' (nonheterosexual or noncisgender) desires and intentions to form families have been under-researched. Further, research on family formation among SGM individuals is even more scant in India. Family formation, a significant milestone for many individuals, has important implications for overall health. Using data from interviews (n=25) and focus group discussions (8 participants) with SGM individuals in Bangalore, Chennai, and Kolkata, we explore desires and intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Seven studies (4%) focused on sexual minority women [ 194 200 ], while two additional studies [ 201 , 202 ] included sexual minority women as part of a larger sample. Among the seven studies, most focused on romantic relationships, such as communication and prioritization in relationships [ 199 ], difficulties in maintaining relationships [ 196 ], understanding of intimacy [ 197 , 198 ], and lack of legal recognition of same-gender romantic partnerships [ 198 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies (4%) focused on sexual minority women [ 194 200 ], while two additional studies [ 201 , 202 ] included sexual minority women as part of a larger sample. Among the seven studies, most focused on romantic relationships, such as communication and prioritization in relationships [ 199 ], difficulties in maintaining relationships [ 196 ], understanding of intimacy [ 197 , 198 ], and lack of legal recognition of same-gender romantic partnerships [ 198 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies (4%) focused on sexual minority women [194][195][196][197][198][199][200], while two additional studies [201,202] included sexual minority women as part of a larger sample. Among the seven studies, most focused on romantic relationships, such as communication and prioritization in relationships [199], difficulties in maintaining relationships [196], understanding in intimate relationships [197,198] and lack of legal recognition of same-gender romantic partnerships [198].…”
Section: Sexual Minority Womenmentioning
confidence: 99%
“…Solomon et al [30] 2010 721 X X X Ghosh et al [31] 2011 32 X X X Sahastrabuddhe et al [32] 2012 84 X X X Ghosh et al [33] 2012 26 X X X Solomon et al [34] 2015 12,022 X X X Mayer et al [35] 2015 307 X X X Hernandez et al [36] 2016 300 X X X Aggarwal et al [37] 2016 52 X X X Solomon et al [38] 2016 12,022 X X X Raghavendran et al [39] 2017 300 X X X Hussain et al [40] 2018 277 X X X Gupte et al [41] 2011 2,633 X X X X Clipman et al [42] 2020 4,994 X X X Haldar et al [43] 2020 2,584 X X X Hernandez et al [44] 2021 302 X X X Palakkal et al [45] 2020 560 X X X Prabhu et al [46] 2021 1,639 X X X Patel et al [47] 2021 20,002 [192] 2020 --X X X Chakrapani et al [193] 2021 360 X X X Bowling et al [194] 2018 67 X X Apoorva et al [195] 2016 8 X X Chithrangathan [196] 2018 1 X X Banerjea [197] 2015 8 X X Bowling et al [198] 2016 20 X X Bowling et al [199] 2018 18 X X Srivastava [200] 2020 25 X X Bowling et al [201] 2019 58 X X X X Bowling et al [202] 2019 33 X X X X Chakrapani et al [203] 2021 27 X X Majumder et al [204] 2021 120 X X X Das [205] 2020 29 X X Joseph et al [206] 2017 205 X X Note: Terminologies for focal populations are derived from original sources, with indigenous sexual and gender identities in italics. GBMSM = Gay, bisexual and other men who have sex with men; TGW = Transgender women; LBWSW = Lesbian, bisexual, and other women who have sex with women; TGM = Transgender men; Ppl with intersex var.…”
Section: Quantitativementioning
confidence: 99%
“…Studies on same-sex family formation and parenting intentions have emerged in many countries. Bowling et al (2019) in India; in Greece, Voultsos et al (2019) analyzed how low social acceptance influences lesbian parenthood; Baiocco & Laghi (2013) show gays and lesbians without children in Italy were less likely than heterosexual individuals to express parenting desires and intentions; Costa & Bidell (2017) found younger participants in their study were more likely to express intent to parent in Portugal; in contrast, young gay men in Germany were less likely than their heterosexual counterparts to report the desire to become fathers (Kranz, Busch & Niepel, 2018); in the United States Tate, Patterson & Levy (2019) also found that in comparison to heterosexual individuals, fewer lesbians and gays intended to become parents and they reported wanting smaller family sizes than their heterosexual peers.…”
Section: Same-sex Familiesmentioning
confidence: 99%